WHY THE UNITED NATIONS HAVE DECLARED THAT 2016 IS THE INTERNATIONAL YEAR OF PULSES? - M. A. Vishnyakova; S. V. Shuvalov (Труды по прикладной ботанике, генетике и селекции)
The paper demonstrates the importance of the VIR grain legumes collection in the context of the International Year of Pulses (IYP) declared by the UN. A range of activities planned by the FAO within the framework of IYP aims to heighten public awareness of the nutritional benefits of pulses, promote their production and trade, stimulate the initiation of new agricultural projects, programs and strategies. The knowledge of modern trends in the use of pulse crops allows making a statement that the VIR collection contains the diversity of this group of crops that may be used for all possible application purposes.